TAX AGGRESSIVENESS IN INDONESIA AND MALAYSIA - Elizabeth Elizabeth; Ernie Riswandari (Berkala Akuntansi dan Keuangan Indonesia, 2022)
Tax aggressiveness is an action taken to reduce or minimizing tax expense to be paid by some sort of scheme. Therefore, this things could cause loss in country revenue where the country did not get the real total revenue. This research is aimed to determined the impact of audit committee, board gender diversity, and profitability on tax aggressiveness. This research used multiple regression analysis method with banking listed firms in Indonesian Stock Exchanges and Malaysian Stock Exchanges as the populations and samples which in total of 45 and 10 firm with non-probability purposive sampling method used which in result of 29 and 10 samples each. This study conduct by checking the listed banking firms in Indonesia Stock Exchanges and Malaysian Stock Exchanges then downloading the financial and annual report of banking listed firms in www.idx.co.id and www.bursamalaysia.com. Audit committee and board gender diversity has no effects on tax aggressiveness both tested in Indonesian Stock Exchanges and Malaysian Stock Exchanges meanwhile profitability has an effects towards tax aggressiveness both in indonesian stock exchanges and malaysian stock exchanges.